Booster cards: A practical tool for unlocking business model innovation - Peter Thomsen; Jesper Chrautwald Sort; Kristian Brøndum (Journal of Business Models (JOBM), 2019)
Business model innovation is an interesting yet challenging teaching area. Both teachers and students encounter barriers, such as dominant logic and a limited level of capabilities. In this paper, we present an analogy-based approach to enhance the teaching process and elevate student motivation using business model stimulus cards.
Keywords: 650; Business models; business model innovation; teaching